ANALYSIS OF IPO PRACTICES IN OUR COUNTRY - Sadullayeva Mohinur (European Science Publishing, 2025)
This article examines the distinctive characteristics of Initial Public Offering (IPO) practices in attracting capital from international financial markets, with a focus on organizing effective capital mobilization and efficient utilization. The characteristics of IPO operations, the timeline of Uzbek companies entering IPOs, and the processes involved in utilizing raised capital have been studied. Scientific conclusions and proposals are presented.
Keywords: Securities, capital, IPO, SPO.